Montali's method: Training block and defense starting with service! - Korteling, B. (The Coach, 1999)
The background of Montali's training session could be described as follows: Block and defense is starting by "service management". After serving the player is going to take his defense position. Even the warming-up of Montali is fully integrated in this subject.